[99mTc]Tc-iFAP Radioligand for SPECT/CT Imaging of the Tumor Microenvironment: Kinetics, Radiation Dosimetry, and Imaging in Patients - Luis Coria-Domínguez; Paola Vallejo-Armenta; Myrna Luna-Gutiérrez; Blanca Ocampo-García; Brenda Gibbens-Bandala; Francisco García-Pérez; Gerardo Ramírez-Nava; Clara Santos-Cuevas; Guillermina Ferro-Flores (MDPI AG, 2022)
Tumor microenvironment fibroblasts overexpress the fibroblast activation protein (FAP). We recently reported the preclinical evaluation of [99mTc]Tc-iFAP as a new SPECT radioligand capable of detecting FAP. This research aimed to evaluate the kinetic and dosimetric profile of [99mTc]Tc-iFAP in healthy volunteers, and to assess the radioligand uptake by different solid tumors in three cancer patients. [99mTc]Tc-iFAP was obtained from lyophilized formulations prepared under GMP conditions with >98% radiochemical purity. Whole-body scans of six healthy subjects were obtained at 0.5, 2, 4, and 24 h after [99mTc]Tc-iFAP (740 MBq) administration. A 2D-planar/3D-SPECT hybrid activity quantitation method was used to fit the biokinetic models of the source organs (volume of interest: VOI) as exponential functions (A(t)VOI). The total nuclear transformations (N) that occurred in the source organs were calculated from the mathematical integration (0,∞) of A(t)VOI. The OLINDA code was used to estimate the radiation doses. Three treatment-naive patients (breast, lung, and cervical cancer) with a prior [18F]FDG PET/CT scan underwent whole-body, chest, and abdominal SPECT/CT scanning after [99mTc]Tc-iFAP (740 MBq) administration. Both imaging methods were compared visually and quantitatively. Oncological diagnoses were performed histopathologically. The results showed favorable [99mTc]Tc-iFAP biodistribution and kinetics due to rapid blood activity removal (t1/2α = 2.22 min and t1/2β = 90 min) and mainly renal clearance. The mean radiation equivalent doses were 5.2 ± 0.8 mSv for the kidney and 1.7 ± 0.3 mSv for the liver after administration of 740 MBq. The effective dose was 2.3 ± 0.4 mSv/740 MBq. [99mTc]Tc-iFAP demonstrated high and reliable uptake in the primary tumor lesions and lymph node metastases in patients with breast, cervical, and lung cancer, which correlated with that detected by [18F]FDG PET/CT. The tumor microenvironment molecular imaging from cancer patients obtained in this research validates the performance of additional clinical studies to determine the utility of [99mTc]Tc-iFAP in the diagnosis and prognosis of different types of solid tumors.